Chemical Characterization and Evaluation of the Anti-Cancer Potential of Flowers from Fridericia platyphylla (Bignoniaceae) - do Rosário, Marcelino S. [UNESP]; Mannochio-Russo, Helena; dos Santos, Ana L.P. [UNESP]; Pinheiro, Aglaete A.; Vasconcelos, Luna N.; Santos, Ana Paula S.A.; de Oliveira, Lila T.; Martins, Monique M.; de Andrade, Marcelo S.; Nascimento, Maria D.S.B.; Bolzani, Vanderlan S. [UNESP]; Lima, Josélia A.; et al. (Sociedade Brasileira de Quimica (SBQ), 2025)
In this study, we aimed to investigate the anticancer activity of the extract, fractions, and isolated compounds of the flowers of Fridericia platyphylla, and to characterize the bioactive compounds. The chemical diversity of the extracts and fractions was investigated using liquid chromatography coupled with high resolution mass spectrometry (LC-HRMS). We were able to annotate 26 compounds from the classes of flavones, flavonols, flavanones, isoflavones, and cinnamic acid and its derivatives. The dichloromethane fraction showed greater cytotoxicity at a concentration of 100 µg mL-1. In addition, the inhibitory concentrations of the dichloromethane fraction were 22.14 and 30.9 µg mL-1 for MCF-7 and MDA-MB-231 cell lines, respectively, and were capable of inhibiting tumor cell migration. Brachydins A and C were isolated from the dichloromethane fraction and showed the greatest cytotoxicity. The results obtained from this study show the potential biological effect of F. platyphylla flowers as a possible antitumor pharmacological agent.
Keywords: Bignoniaceae; brachydins; cancer; flavonoids; spectral annotation